ANALISIS KINERJA KEUANGAN UD. GUNUNG MAS SAMARINDA - Guantemala, Channie (EKONOMIA, 2012)
Problem solving and hypothesis verification is done by analyzing financial ratios UD. Gunung Mas Samarinda consisting of Liquidity Ratios (Current Ratio, Quick Ratio, Cash Ratio) Leverage Ratios (Debt to Operating Cash Flow, Total Debt to Total Assets, Stockholder's Equity Ratio), and Profitability Ratios (Net Profit Margin, Return on Equity, Return on Total Assets), as well as the percentage per component analysis is done by comparing an item to the total in the same financial statements to calculate the growth and financial performance of UD. Gunung Mas Samarinda from 2006 to 2011.The results of the analysis showed that there was a tendency on average improvement of UD. Gunung Mas Samarinda financial performance measured by Liquidity Ratio and Leverage Ratio 2006 to 2011. Based on these explanations, the first and the second hypothesis are accepted. But there is a tendency of the average decline in Profitability Ratios which mean the financial performance of UD. Gunung Mas Samarinda has decreased.